Failure Analysis of the Pin Bore of the Combined Piston for the Aero Engine - Zhongjian Pan; Lei Guo (International Journal of Aerospace Engineering)
The combined piston can be used in an aero piston heavy fuel engine because of its light weight, so as to reduce the reciprocating inertia force and improve the engine power-weight ratio. However, the pin bore of the combined piston is prone to deform leading to the failure of the piston. Based on the structure of the piston, the stress of the piston under thermomechanical coupling is analyzed, the temperature field of the piston is determined by experiments, and the deformation rule of the piston pin bore under the thermomechanical coupling is summarized. A design scheme is proposed to change the position of the thread connection between the piston crown and the piston head. Under the same conditions, the deformation of the piston pin bore of the original scheme and the new scheme is analyzed. The results show that together with the changing of the connection thread between the piston crown and the piston head, the deformation of the piston pin bore decreases by 60 μm and the deformation of the piston pin bore is controlled. The test results show that the deformation of the pin bore is within the acceptable range, which proves the effectiveness of the improved scheme.